Hirayama Disease: Imaging Profile of Three Cases Emphasizing the Role of Flexion MRI - Sarawagi, Radha (JCDR Research and Publications (P) Limited, 2014)
We report three cases of Hirayama disease, cervical flexion myelopathy presenting as unilateral or bilateral asymmetric muscular atrophy of forearm and hand involving C7 - T1 myotomes in young males. MRI revealed asymmetric cord atrophy, altered signal intensity of cord, posterior dural detachment and enlarged posterior epidural space with multiple flow voids. This article emphasizes the role of Flexion MRI in diagnosing Hirayama disease.